2019
DOI: 10.1186/s12978-019-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictors of domestic violence among pregnant women in Southeast Oromia, Ethiopia

Abstract: IntroductionDomestic violence is a common global health problem and relatively hidden and ignored form of violence against pregnant women. The magnitude of domestic violence among pregnant women is higher in low and middle-income countries including Ethiopia as compared with developed countries. Domestic violence is a violation of human right and associated with numerous adverse outcomes for mothers and the offspring. However, research on domestic violence and predictors against pregnant women is limited in Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 24 publications
(35 reference statements)
5
21
9
Order By: Relevance
“…A woman who saw family violence as childhood was 2.2 times more likely to experience domestic violence. This nding was consistent with a previous study conducted in Nigeria (15), southeast Oromia (29), and North West Ethiopia (31) but, lower than a study conducted in Ghana (5). The difference of results between the current study and the study in Ghana ay be due to population differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A woman who saw family violence as childhood was 2.2 times more likely to experience domestic violence. This nding was consistent with a previous study conducted in Nigeria (15), southeast Oromia (29), and North West Ethiopia (31) but, lower than a study conducted in Ghana (5). The difference of results between the current study and the study in Ghana ay be due to population differences.…”
Section: Discussionsupporting
confidence: 92%
“…This nding is in line with a previous study conducted on 14 sub-Saharan countries (27), with a study conducted in Ghana (5), Nigeria (15), Zambia (6), a systematic review of 15 articles in Ethiopia (8) and a study conducted in Robe Hospital, southeast Ethiopia (28). The result of this study is lower than a study conducted in southeast Oromia (29) and in northwest Ethiopia (16). This difference may be due to differences in the study population (because the previous studies are conducted mainly among pregnant women) and sample size differences (the current study was employed on a large sample size).…”
Section: Discussioncontrasting
confidence: 62%
“…(2013) study in Turkey, the Boru Bifftu et al (2017) study in northwest Ethiopia, as well as the results of two studies in 2016 and 2019 in Nepal were consistent with the present study and showed that the level of domestic violence against pregnant women was low in these regions [15,16,20,29]. But the Yohannes et al (2019) study in southeastern Ethiopia and the Fekadu et al (2018) study in northwest Ethiopia found that the rate of domestic violence against pregnant women was high in these regions [17,30].…”
Section: Discussionsupporting
confidence: 89%
“…The results of the studies showed that the most common type of violence was sexual one and then psychological and emotional violence [14,17,20,29] which were in line with the present study. But Yohannes et al's (2019) study in southeastern Ethiopia was not consistent with the present study which showed that physical violence had the highest rate of violence among pregnant women [30]. Also, the results of Hassan et al (2013) study showed that physical violence and psychological violence were the most common types of violence in this study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation